Microfluidic organ-on-chip systems for periodontal research: advances and future directions - Sriram, Gopu; Makkar, Hardik (Frontiers in Bioengineering and Biotechnology, 2025)
Advances in tissue engineering and microfluidic technologies have enabled the development of sophisticated in vitro models known as organ-on-a-chip (OoC) or microphysiological systems. These systems enable to potential to simulate the dynamic interactions between host tissues and their microenvironment including microbes, biomaterials, mechanical forces, pharmaceutical, and consumer-care products. These fluidic technologies are increasingly being utilized to investigate host-microbe and host-material interactions in oral health and disease. Of interest is their application in understanding periodontal disease, a chronic inflammatory condition marked by the progressive destruction of periodontal tissues, including gingiva, periodontal ligament, and alveolar bone. The pathogenesis of periodontal disease involves a complex interplay between microbial dysbiosis and host immune responses, which can lead to a loss of dental support structures and contribute to systemic conditions such as cardiovascular disease, diabetes, and inflammatory bowel disease. This provides a comprehensive overview of the latest developments in millifluidic and microfluidic systems designed to emulate periodontal host-microbe and host-material interactions. We discuss the critical engineering and biological considerations in designing these platforms, their applications in studying oral biofilms, periodontal tissue responses, and their potential to unravel disease mechanisms and therapeutic targets in periodontal disease.